1954
DOI: 10.1139/v54-073
|View full text |Cite
|
Sign up to set email alerts
|

Spectres d'ABSORPTION Infrarouges Des Urées Substituées

Abstract: not available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1960
1960
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…B. Vibrational Analysis of Crystalline DMU . The infrared spectrum of DMU has been described for the first time in 1954 …”
Section: The Vibrational Spectrum Of Dmumentioning
confidence: 99%
See 1 more Smart Citation
“…B. Vibrational Analysis of Crystalline DMU . The infrared spectrum of DMU has been described for the first time in 1954 …”
Section: The Vibrational Spectrum Of Dmumentioning
confidence: 99%
“…The infrared spectrum of DMU has been described for the first time in 1954. 14 In this study Boivin tried to deduct the characteristic vibrational bands of the CH 3 NHCONH group by comparing a series of urea derivatives of the type RNHCONHCH 3 (R ) alkyl, aryl). In 1956, Becher 15 deducted a coupling between the ν as C-N and the δ as N-H vibrations by comparing the infrared spectra of normal and deuterated DMU.…”
Section: The Vibrational Spectrum Of Dmumentioning
confidence: 99%
“…dibutylureas. Though a number of the papers26•[29][30][31][32][33] concerned with the spectra of urea derivatives have been presented, it is not possible to interpret fully the intricacies of the results and there are different opinions for the assignment of amide band II.26•30 However, all urea derivatives have the amide band I arising from the CO group and those which possess at least one hydrogen atom at the nitrogen atom of the urea linkage have the amide band II arising from the NH deformation. Boivin and his co-worker have measured the infrared spectra of the types of CH3NHCONHR, and concluded that these compounds had an amide band I in 1620-1660 cm.-1 and an amide band II in 1580-1630 cm.,-1 respectively.…”
mentioning
confidence: 99%